Applications of aluminosilicate and zincosilicate materials: aqueous phase ion exchange and gas phase adsorption - Selbe, Tyler J. (Kansas State University, 2010)
Zeolites and zeolite-like materials have well-ordered structures and pores creating varying capacities for molecules based upon size, functional groups, polarity, and intermolecular forces making the materials useful for molecular sensing as well for molecules that are considered hazardous at very low concentrations with reproducible results because of these properties. This study will identify and characterize applications for zeolite and zeolite-like materials in gas and liquid phases based upon the dominating physical and chemical properties of the materials. The properties of interest include liquid phase ion exchange capacities, selectivities, gas/vapor phase adsorption capacity, and initial adsorption uptake rate. Zincosilicates have similar framework structures to aluminosilicate zeolites; however, they have distinct advantages over traditional zeolites. Zincosilicates typically have a higher ion density, lack “cages” in their structure which leads to all the cations being accessible for ion exchange, and have the ability to form three-membered rings which lead to large void spaces in their structure. These features lead to high capture capacities for divalent heavy metal mercury ions. In this work, the potential to use zincosilicates as ion exchangers such as VPI-7, VPI-9 and VPI-10 is presented. Results have shown that zincosilicates have capture capacities greater than traditional zeolites, even greater than those that have been synthesized with functional groups intended to increase metal sorption capacities. The selectivity coefficients in a binary ion exchange system were successfully modeled using the Gibbs-Donnan selectivity model. The selectivities for the zincosilicates were Pb>Na>Hg>K>Ca. Zeolites are also able to adsorb chemical species and therefore can be used as the recognition element in sensing devices. The sorption capacity of 2-chloroethyl ethyl sulfide, dimethyl methanephosphonate, ethanol, and n-butanethiol were examined with zeolites 13X, 4A, MCM-41, VPI-7, VPI-9, and ZSM-5. The zeolites selected provided very different framework composition, countercation, and surface area features for determining the most significant properties in adsorption. Zeolite 13X had the highest equilibrium and initial uptake rate for most compounds tested, whereas the low surface area zincosilicates, VPI-7 and VPI-9, had the lowest capacity. Based on these results, a piezoelectric device with an array of zeolites can be successfully employed as a sensor.
Keywords: Ion Exchange; Chemical Warfare Agent; Mercury; Adsorption; Chemistry, Inorganic (0488); Engineering, Chemical (0542)